Human Cord Blood-Derived Stem Cells in Transplantation and Regenerative Medicine - Iancu, Cornel; Ilie, Ioana; Mocan, Lucian; Georgescu, Carmen; Ilie, Razvan; Duncea, Ileana; Mocan, Teodora; Iancu, Dana; Zaharie, Florin (IntechOpen, 2011)
None